Ice breaking by a collapsing bubble. (23rd February 2018) - Cui, Pu; Zhang, A-Man; Wang, Shiping; Khoo, Boo Cheong
Abstract : This work focuses on using the power of a collapsing bubble in ice breaking. We experimentally validated the possibility and investigated the mechanism of ice breaking with a single collapsing bubble, where the bubble was generated by underwater electric discharge and collapsed at various distances under ice plates with different thicknesses. Characteristics of the ice fracturing, bubble jets and shock waves emitted during the collapse of the bubble were captured. The pattern of the ice fracturing is related to the ice thickness and the bubble–ice distance. Fractures develop from the top of the ice plate, i.e. the ice–air interface, and this is attributed to the tension caused by the reflection of the shock waves at the interface. Such fracturing is lessened when the thickness of the ice plate or the bubble–ice distance increases. Fractures may also form from the bottom of the ice plate upon the shock wave incidence when the bubble–ice distance is sufficiently small. The ice plate motion and its effect on the bubble behaviour were analysed. The ice plate motion results in higher jet speed and greater elongation of the bubble shape along the vertical direction. It also causes the bubble initiated close to the ice plate to split and emit multiple shock waves at the end of the collapse. The findings suggest that collapsing bubbles can be used as a brand new way of ice breaking.